2019
DOI: 10.1016/j.jclepro.2019.117732
|View full text |Cite
|
Sign up to set email alerts
|

Learning about spatial inequalities: Capturing the heterogeneity in the urban environment

Abstract: Highlights-A multidimensional approach evidence different level of inequalities distribution -Groups with diverse socioeconomic condition of accessibility to services are mapped -Spatial inequalities of a global south megacity São Paulo (Brazil) are explored -Low income groups have low accessibility mainly to hospitals and culture centers -A heterogeneous condition of accessibility and income in the periphery is captured Graphical abstract 3 LEARNING ABOUT SPATIAL INEQUALITIES: CAPTURING THE HETEROGENEITY IN T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Continuity was also observed as a factor for mental health in O'Campo et al [32], who used conceptual mapping to highlight the importance of maintaining access to local amenities and services for positive mental wellbeing, especially in the most disadvantaged neighbourhoods. Similarly, another study [53] found that "access" is experienced differently by groups of low or high socioeconomic status based on land use and transport design. The need for spatial and temporal continuity highlighted in some of the included studies also suggests the relevance of using a systems approach to ensure a sustainable urban change, as discussed by Pérez del Pulgar [46], which is in line with growing calls for an ecological and systems-based approach to urban development [54].…”
Section: Discussionmentioning
confidence: 90%
“…Continuity was also observed as a factor for mental health in O'Campo et al [32], who used conceptual mapping to highlight the importance of maintaining access to local amenities and services for positive mental wellbeing, especially in the most disadvantaged neighbourhoods. Similarly, another study [53] found that "access" is experienced differently by groups of low or high socioeconomic status based on land use and transport design. The need for spatial and temporal continuity highlighted in some of the included studies also suggests the relevance of using a systems approach to ensure a sustainable urban change, as discussed by Pérez del Pulgar [46], which is in line with growing calls for an ecological and systems-based approach to urban development [54].…”
Section: Discussionmentioning
confidence: 90%
“…Accessibility to leisure and its inequalities has been the subject of study of a few researchers, with a special focus on parks and green areas (Siqueira-Gay et al, 2019; Wang and Lan, 2019; Wei, 2017; Xing et al, 2018). The distribution of leisure opportunities has become an important issue in spatial planning with the growing concern of urban population with quality of life (De Vries et al, 2003).…”
Section: Accessibility To Leisure and Inequalitiesmentioning
confidence: 99%
“…The authors found that walking accessibility to cultural centers has a positive impact on housing prices, which can lead to accessibility inequalities related to income. In a similar line, Siqueira-Gay et al (2019) investigated spatial inequalities in accessibility to several opportunities, including cultural centers, in São Paulo, Brazil. Results indicated that the low-income population has low access to cultural centers.…”
Section: Accessibility To Leisure and Inequalitiesmentioning
confidence: 99%
“…In addition, He & Zhang [36] also said that the relation between the urbanization process and inequality is developed by the distribution effects of urbanization. Siqueira-Gay et al [37] argue that inequality is related to the distribution of opportunities among people and places, and since the territory is the spatial area in which the people live, then territory becomes an important the ground where the distribution of the opportunities should be allocated, then the spatial point of view also becomes an important aspect in the discourse of inequality. Furthermore, Senoret et al [38] argue that fragmentation characteristics of the cities bring influence the existence of inequality within cities, and Yin et al [39] said that spatial inequality is also contributed by unequal spatial accessibility, while Siqueira-Gay et al [38] said that accessibility provides potential opportunities for interaction that spatially links the integration of environmental issues and social issues.…”
Section: Introductionmentioning
confidence: 99%